Effect of Output Coupling Reflectivity on Performance of L-band Erbium-doped Fiber Laser - Harun, Sulaiman Wadi; Chong, Wu Yi; Subramaniam, T.; Ahmad, Harith (De Gruyter, 2006)
An effect of output coupling reflectivity on performance of L-band erbium-doped fiber laser is demonstrated. An increase of reflectivity induces operating wavelength to shift to a longer wavelength. However, the threshold pump power and laser output power reduces with the increase of reflectivity. When a reflectivity and pump power are fixed at 60% and 13.9 mW, respectively, the lasing wavelength is obtained at 1592 nm with an output power of -4.6 dBm, a 3 dB spectrum width of about 0.06 nm and SMSR of about 32 dB. The highest slope efficiency of 18.4% is obtained for the cavity with 20% of output coupler reflectivity.